Plasmatic tissue factor pathway inhibitor is a major determinant of clotting in factor VIII inhibited plasma or blood - Knappe, Sabine; Gorczyca, Monika E.; Jilma, Bernd; Derhaschnig, Ulla; Hartmann, Rudolf; Palige, Michael; Scheiflinger, Fritz; Dockal, Michael (Thrombosis and Haemostasis, 2013)
Tissue factor pathway inhibitor (TFPI) is a major inhibitor of coagulation. We therefore hypothesised that high plasmatic TFPI levels are associated with impaired ex vivo clotting in a model of acquired haemophilia. Blood samples were collected in a prospective clinical study from 30 healthy volunteers. Coagulation in normal or factor VIII (FVIII)-inhibited human blood or plasma was measured by the calibrated automated thrombogram (CAT) and rotational thromboelastometry (ROTEM). Both methods are global haemostatic assays that provide insight into the whole coagulation process. Monoclonal mouse antibodies raised against either the C-terminus or the Kunitz domain 2 of TFPI were used to determine full-length (fl-) and total TFPI by an enzyme-immunoassay. Clotting times and parameters of thrombin generation correlated with TFPI levels. Subjects with low fl-TFPI levels had significantly shorter clotting times and a higher endogenous thrombin potential (ETP) compared to those with high fl-TFPI levels (p≤0.005 for all). An even stronger effect was seen in FVIII-inhibited blood/plasma: ROTEM clotting time was 26% shorter (p=0.01) and the ETP assessed by CAT was >2-fold higher in subjects with low fl-TFPI levels (p≤0.0001). Plasmatic TFPI is a major determinant of coagulation in global haemostatic tests particularly when FVIII is missing. Thus, inhibition of TFPI might be a promising novel treatment approach, especially in haemophilia patients with FVIII inhibitors.
Keywords: Tissue factor pathway inhibitor; TFPI; coagulation factor FVIII; calibrated automated thrombin generation assay (CAT); rotational thromboelastometry (ROTEM); haemophilia